Legal Uncertainty and Barriers to Women's Representation in Village Governance: Ketidakpastian Hukum dan Hambatan Keterwakilan Perempuan dalam Tata Kelola Pemerintahan Desa - Mulyono, Edy; Widodo, Hananto; Rusdiana, Emmilia; Prasetio, Dicky Eko (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Women's representation in Indonesia's Village Consultative Bodies (BPD) is essential for gender equality and inclusive governance. However, unclear regulations, socio-cultural barriers, and weak enforcement hinder progress. Gap: Legal ambiguities and inconsistent practices limit effective participation and gender-responsive decision-making. Aim: This study explores the legal uncertainties affecting women's representation in BPDs and their broader impacts. Results: Findings highlight unclear legislation, gaps between national and regional regulations, and insufficient enforcement, compounded by cultural biases, reducing women’s motivation and participation. Novelty: The study provides a unique analysis of legal and socio-cultural challenges, offering actionable reform strategies. Implications: Clearer regulations and empowerment programs can improve representation, fostering equitable governance and sustainable development. Highlights: Legal ambiguities in regulations hinder women’s effective participation in BPDs. Socio-cultural biases significantly reduce opportunities for gender-responsive governance. Clearer policies and empowerment programs are vital for equitable local development. Keywords: Women's Representation, Village Consultative Bodies, Gender Equality, Legal Uncertainty, Governance